Spatial Quantile Regression; Przestrzenna regresja kwantylowa - Grazẏna Trzpiot (Comparative Economic Research. Central and Eastern Europe, 2012)
In a number of applications, a crucial problem consists in describing and analyzing the influence of a vector Xi of covariates on some real-valued response variable Yi. In the present context, where the observations are made over a collection of sites, this study is more difficult, due to the complexity of the possible spatial dependence among the various sites. In this paper, instead of spatial mean regression, we thus consider the spatial quantile regression functions. Quantile regression has been considered in a spatial context. The main aim of this paper is to incorporate quantile regression and spatial econometric modeling. Substantial variation exists across quantiles, suggesting that ordinary regression is insufficient on its own. Quantile estimates of a spatial-lag model show considerable spatial dependence in the different parts of the distribution. – – W wielu zastosowaniach, podstawowym problemem jest opis i analiza wpływu wektora skorelowanych zmiennych objasńiajacych X na zmienna objasńiana Y. W przypadku, gdy obserwacje badanych zmiennych sa dodatkowo rozmieszczone przestrzennie, zadanie jest jeszcze trudniejsze, poniewazṁamy dodatkowe zalezṅosći, wynikajace ze zmiennosći przestrzennej. W tej pracy, w miejsce przestrzennej regresji wykorzystujacej sŕednia, rozpatrzymy przestrzenna regresje kwantylowa. Regresja kwantylowa zostanie omoẃiona w przestrzennym konteksćie. Głoẃnym celem pracy jest wskazanie na mozl̇iwosći powiazania metodologii regresji kwantylowej i ekonometrycznego modelowania przestrzennego. Dodatkowe zasoby informacji o zmiennosći otrzymujemy badajac kwantyle, wychodzac poza tradycyjny opis klasycznej regresji. Estymacja kwantylowa w modelu przestrzennym uwydatnia zalezṅosći przestrzenne dla roźṅych fragmentoẃ rozwazȧnych rozkładoẃ.
Keywords: 330